2001
DOI: 10.1016/s0035-9203(01)90229-9
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic dengue transmission in southern Sumatra, Indonesia

Abstract: An outbreak of dengue fever (DF), dengue haemorrhagic fever (DHF), and dengue shock syndrome (DSS) in the city of Palembang, south Sumatra, Indonesia was investigated to (i) validate epidemic occurrence, (ii) confirm dengue virus aetiology and associated serotype(s), (iii) provide a demonstrable measure of community impact, and (iv) identify causative relationship (if any) with climatic El Niño Southern Oscillation (ENSO) influences. Trend analysis based on a 6-year retrospective review of hospital records dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
3
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 19 publications
7
63
3
6
Order By: Relevance
“…In congruence with the present study, Corwin et al 25 also found that Den-1 is associated with less severe disease. Several reports from other countries articulating differences in disease severity associated with distinct dengue serotypes support our results.…”
Section: Discussionsupporting
confidence: 93%
“…In congruence with the present study, Corwin et al 25 also found that Den-1 is associated with less severe disease. Several reports from other countries articulating differences in disease severity associated with distinct dengue serotypes support our results.…”
Section: Discussionsupporting
confidence: 93%
“…5 This was also evident during the 1993-1994 outbreak reported from Papua, although DEN-1 and DEN-2 viruses were also detected.…”
Section: Introductionmentioning
confidence: 78%
“…9 The implication as to the predominance of DEN-3 virus in association with DHF was documented in other instances of epidemic DHF occurrences in Indonesia, including the Palembang and Jayapura outbreak. 4,5 The predominance of DEN-3 virus in this and other outbreak findings throughout Indonesia may represent a sampling bias because most specimen collections have targeted inpatient populations who present more severe clinical hemorrhagic manifestations. While there may indeed be a virulence component associated with an infecting viral serotype, it is also recognized that other serotypes may be more prevalent among less severe cases.…”
Section: Hospital Case Detection Clinical Epidemiologymentioning
confidence: 97%
See 1 more Smart Citation
“…This is a problem that needs to be addressed since adult disease is not just confined to travelers from developed countries. In Southeast Asia, dengue primarily affects the adult population in Singapore 39,40 , while the average age of infection has been observed to be increasing in other places 41,42 . Notwithstanding the current debate over the WHO case definition, there is also no consistency in the way these definitions are applied across dengue-endemic countries.…”
Section: Current Developments In Southeast Asiamentioning
confidence: 99%